2015
DOI: 10.3174/ajnr.a4354
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and White Matter Tract Differences in MS and Diffuse Neuropsychiatric Systemic Lupus Erythematosus

Abstract: BACKGROUND AND PURPOSE:Multiple sclerosis and neuropsychiatric systemic lupus erythematosus are autoimmune diseases with similar CNS inflammatory and neurodegenerative characteristics. Our aim was to investigate white matter tract changes and their association with cognitive function in patients with MS and those with neuropsychiatric systemic lupus erythematosus compared with healthy controls by using diffusion tensor imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…DTI studies have suggested WM damage in well-defined NP SLE patients, particularly in areas of the frontal lobe, frontobasal and temporal WM tracts, and the corpus callosum (CC). [16][17][18][19][20] Studies in SLE patients without NP activity have also demonstrated DTI abnormalities. Compared to controls, lower FA was found in SLE patients without NP in the right cingulum, 21 normal appearing WM, 22 right superior coronal radiata, the right superior longitudinal fasciculus, the body of the CC, the right inferior fronto-occiptal fasciculus, the right thalamic radiation, the right uncinate fasciculus, 23 and in the CC genu and left corticospinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…DTI studies have suggested WM damage in well-defined NP SLE patients, particularly in areas of the frontal lobe, frontobasal and temporal WM tracts, and the corpus callosum (CC). [16][17][18][19][20] Studies in SLE patients without NP activity have also demonstrated DTI abnormalities. Compared to controls, lower FA was found in SLE patients without NP in the right cingulum, 21 normal appearing WM, 22 right superior coronal radiata, the right superior longitudinal fasciculus, the body of the CC, the right inferior fronto-occiptal fasciculus, the right thalamic radiation, the right uncinate fasciculus, 23 and in the CC genu and left corticospinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that SLE patients mainly experience difficulties in attention, information processing, learning, memory, and executive functions (Ainiala, Loukkola, Peltola, Korpela, & Hietaharju, 2001; Kozora et al, 2005;Kozora, Arciniegas, et al, 2008) and that SLE-patients, similar to patients suffering from multiple sclerosis, tend to show relatively well-preserved verbal functions (Cesar et al, 2015;Hanly, Omisade, Su, Farewell, & Fisk, 2010;Papathanasiou, Messinis, Georgiou, & Papathanasopoulos, 2014).…”
mentioning
confidence: 99%
“…Neuroimaging and cognitive correlates of NPSLE have been examined with magnetic resonance imaging (MRI) in order to understand its mechanisms. MRI experiments have demonstrated NPSLE‐associated alterations, including white matter hyperintensities suggestive of vascular disease and diffuse gray matter lesions that may be consequent to immunological responses or seizures .…”
mentioning
confidence: 99%